Learning Styles a Potential Predictor of Student Achievement in Remote and Virtual Laboratory Classes - Lindsay, Euan; Good, M. (Australasian Association for Engineering Education, 2007)
Remote and virtual laboratories are becoming increasingly prevalent as ways of providing engineering students with the laboratory learning experience. Previous literature suggests that there may be differences in the nature of these learning experiences, leading to difference in the learning outcomes achieved by students exposed to these different access modes.This paper investigates the impact of the students' preferred learning styles upon these changes in learning outcomes. This study shows that for some learning outcomes, the differences are not dependent solely upon access mode, but rather upon the interaction of access mode and learning style. Some styles are more susceptible to mode-based variations, whilst others show little change between the modes. This suggests that the students' preferred learning styles may be a potential diagnostic tool for determining which access mode will most enhance a given student's learning opportunities.